Efficient Raman scattering response and large piezoelectricity in noncentrosymmetric MnHg(SCN)4 crystals. Issue 13 (20th March 2017) - Liu, Xitao; Long, Peiqing; Wang, Xinqiang; Gao, Zeliang; Lü, Yadong; Yi, Zhiguo
Abstract : Noncentrosymmetric MnHg(SCN)4 crystals show an efficient Raman scattering response and large piezoelectricity. Abstract : Organic–inorganic hybrid materials crystallized in noncentrosymmetric (NCS) structures have been receiving considerable attention due to their fascinating physical properties and promising applications. Herein, bulk single crystals of an NCS organometallic compound, MnHg(SCN)4 (MMTC), are grown via a temperature lowering method. The grown crystals present negative uniaxial characteristics with large birefringence, good optical homogeneity and high thermal conductivities. In addition, their Raman scattering properties are measured using spontaneous Raman spectroscopy, which show that the MMTC crystal exhibits a large Raman shift (2148.1 cm −1 ), narrow line-width (4.468 cm −1 ) and high Raman gain coefficient (1.753 times higher than that of crystalline YVO4 ). Moreover, the direct current conductivity, dielectric, and piezoelectric constants of MMTC are also measured, which display that the crystal also possesses a strong piezoelectric response of d 15 = 22.7 pC N −1 . Furthermore, structure property relationships are discussed on the basis of the structure of the crystal. As a multi-functional crystal, MMTC is a particularly promising candidate for stimulated Raman scattering in the visible and near-infrared regions and piezoelectric applications at room temperature.